Gestational and lactational exposure to triclosan causes impaired fertility of F1 male offspring and developmental defects in F2 generation. (February 2020) - Priyanka,; Trivedi, Ayushi; Maske, Priyanka; Mote, Chandrashekhar; Dighe, Vikas
Abstract: Triclosan (5-chloro-2-(2, 4-dichlorophenoxy) phenol, TCS), is a broad-spectrum antimicrobial agent and extensively used in household and daily daycare products. Recently, several reports have demonstrated the endocrine disruptive action of TCS to alter the testicular steroidogenesis. However, the gestational and lactational effects of TCS exposure on F1 offspring has not been studied. Present study aimed to investigate the effect of gestational and lactational exposure to TCS on F1 male progeny and its effect on fertility. Pregnant dams (F0) were administered with different doses of TCS (0.1, 4, 40 and 150 mg/kg b. wt./day) and Diethylstilbestrol (1 μg/kg b. wt./day), as a positive control daily by subcutaneous injection during Gestation Day 6 to Postnatal Day 21. Delayed testicular descent was observed at 150 mg/kg b. wt./day dose group. Dose-dependent decrease in testosterone level, sperm count and motility was observed. Significantly decreased expression of steroid hormone receptors (AR, ERα and ERβ), StAR and aromatase were observed in F1 male rats; indicating its prolonged effect on spermatogenesis and steroidogenesis in adulthood and poor development in F2 fetuses. Further, gestational and lactational exposure to TCS has negative impact on the fertility of F1 male rats. The F1 male rats were found sub-fertile with increased (%) pre- and post-implantation loss (at 40 and 150 mg/kg b.wt./day dose) with a simultaneous decrease in litter size. The significant decrease in mean fetal weight and crown-rump length (CRL) of F2 fetuses were observed at 0.1, 4, 40 and 150 dose groups indicating impaired development of F2 fetuses caused by TCS exposure. Present study emphasizes for the first time that TCS exposure during the vulnerable developmental time point (gestation and lactation) adversely affects reproductive functions and fertility of F1 male rats, which were transmitted to F2 generations leading to reduced CRLs and weights of F2 fetuses. Graphical abstract: Image 1 Highlights: Exposure to TCS caused delay in testis descent in F1 male rats. TCS negatively affects the sperm count and motility in the F1 male rats at PND 75. TCS exposure perturbed expression of steroid hormone receptors, StAR and aromatase. Subfertility with increased (%) pre- and post-implantation loss in F1 male rats. TCS exposure caused decrease in fetal weight and crown-rump length of F2 fetuses.